DILĀLAH MANṬŪQ DAN MAFHŪM DALAM USHUL FIKIH: (KAJIAN KOMPARATIF MAZHAB DAN IMPLIKASINYA TERHADAP ISTINBATH HUKUM ISLAM) - Rahmatul Qadri; Fatmawati; Rauf Amin (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
This article aims to analyze the concepts of manṭūq and mafhūm from the perspective of Islamic legal theorists and to examine their implications for Islamic legal reasoning. This study employs a library research method with a descriptive-analytical approach, drawing upon classical and contemporary works on Islamic legal theory. The findings reveal that manṭūq and mafhūm function not only as linguistic tools for understanding legal texts but also as epistemological instruments that shape legal interpretation and reasoning. The analysis of scholarly perspectives indicates a consensus regarding the authoritative status of manṭūq, while discussions on mafhūm have generated diverse approaches in its application and development. These differences have implications for methods of legal inference and contribute to the diversity of juristic opinions. This study demonstrates that the discourse on manṭūq and mafhūm occupies a significant position in bridging the relationship between text, methodology, and the formulation of Islamic law.